Efficient Ring-Cavity Terahertz Parametric Oscillator With Pump Recycling Technique - Longhuang Tang; Degang Xu; Yuye Wang; Chao Yan; Yixin He; Zhongcheng Sun; Ci Song; Kai Zhong; Jianquan Yao (IEEE Photonics Journal)
The energy scaling of THz wave in wide range based on surface-emitted (SE) ring-cavity terahertz parametric oscillator (TPO) with pump recycling technique is demonstrated in this paper. The continuously tunable range from 1.24 to 3.77 THz was achieved with full pump beam recycling, whereas the tunable range was 1.24–2.72 THz without pump beam recycling. The terahertz output energy and conversion efficiency increased more than seven times throughout the whole tuning range. The maximum enhancement ratio of the terahertz output energy was 12.8 times at 2.72 THz. Additionally, under the same experimental conditions, THz conversion efficiency was increased from 7.77 × 10−6 to 7.85 × 10−5 and the threshold energy was significantly reduced by 41% at 1.63 THz. Moreover, through the theoretical analysis, the enhancement mechanism of TPO by pump recycling was verified to originate from the threshold reduction of the stimulated polariton scattering (SPS) process and the interaction improvement between the pump and Stokes waves in the difference frequency generation (DFG) process.